Studi Literatur: Efektivitas Mediasi Sebagai Alternatif Penyelesaian Sengketa Bisnis di Luar Pengadilan - Edo Arya Prabowo (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This research aims to describe the effectiveness of mediation as an alternative to out-of-court business dispute resolution. This research was conducted using the literature study method. The results show that the use of mediation as an alternative to out-of-court dispute resolution has effectiveness because in the implementation of non-litigation mediation, the examination of the two parties is carried out behind closed doors (not open to the public). Thus, the positive impact is that the credibility and reputation of the parties to the dispute are maintained. In addition, compared to the litigation process, out-of-court mediation is relatively cheaper, less complicated, and does not take a long time. On the other hand, out-of-court mediation pays great attention to the continuity of the parties' relationship in the future. This is the reason why business people favor out-of-court mediation as an alternative to resolving their business disputes.